Reduced‐Dimensional Engineering toward 2D R‐P (OAm)2CsPb2Br7 Perovskite by Metal Ion Enabled Ligands Confinement Effect. Issue 11 (2nd March 2022) - Gao, Xupeng; Hu, Qiang; Li, Xin; Lu, Po; Zhong, Yuan; Shen, Xinyu; Yu, William W.; Lu, Min; Wu, Zhennan; Yu, Siyao; Bai, Xue; Zhang, Yu
Abstract: The dimension is a leading parameter in customization of unique optoelectronic properties of halide perovskite, while it is still challenging to achieve dimension control beyond the well‐developed composition regulation‐based strategy considering their intrinsic feature of ionic crystal. In this paper, ligands‐directed confinement effect is emphasized in rendering the reduced‐dimensional engineering of halide perovskite, and quasi‐2D (OAm)2 CsPb2 Br7 ( n = 2) nanosheets are obtained by introducing a large amount of metal ions. As a representation, with Mg 2+ participation, the initial adsorption of organic ligands (i.e., OA and OAm) to inorganic components (i.e., [PbBr6 ] 4− ) is promoted, conferring a ligands‐directed surface reconstruction to form the lamellar structure composed of alternate organic and inorganic layers. Namely, the inorganic–organic lamellar ensemble will play as a soft template, which effectively restricts the growth of [PbBr6 ] 4− in the c ‐axis direction even after the Cs‐OA injection, thus producing the anisotropic layered perovskite of (OAm)2 CsPb2 Br7 from CsPbBr3 scenario. Notably, such reduced‐dimensional engineering enables a remarkable luminescence tailoring, of which the deep blue emission centered at 439 nm is achieved. In addition, benefiting from such universal strategy, the luminescence is also dependent on the species of introduced metal ions (e.g., Ca 2+, Co 2+, Sr 2+, and Mn 2+ ). Abstract : The ligands‐directed confinement effect is emphasized in rendering the reduced‐dimensional engineering of halide perovskite, by performing a transformation from typical 3D CsPbBr3 quantum dots to 2D Ruddlesden–Popper perovskite (OAm)2 CsPb2 Br7 ( n = 2) nanosheets driven by significant introduction of metal ions.